Factors influencing plateletpheresis donations in Yogyakarta, Indonesia - Aditya Wicaksana; Teguh Triyono; Umi Intansari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Despite its life saving potential, regrettably, blood transfusion has yet to be optimally applied in Indonesia. Funding difficulties and both public and professional lack of knowledge hinders its progress. More lives can be saved by using a safer, more proper, and specialized blood transfusion procedure. Plateletpheresis, one method to obtain platelet products, requires a different donation procedure than that of whole blood-derived platelet. High quality plateletpheresis product donation will positively impact the transfusion efficacy and platelet recovery of the recipient, improving patient’s clinical state. This study analyzes factors from both the donor and donation procedure that influence the quality of plateletpheresis product. The study analyzes data of plateletpheresis donations from blood transfusion service and plateletpheresis transfusions from medical records at Dr. Sardjito General Hospital, Yogyakarta, Indonesia, within the period of August 2012 to January 2013 using cross sectional design. Forty-four plateletpheresis donations were obtained during the study. All donors were male with the following mean values; age 31.9 ± 9.9 years, weight 70.2 ± 10.2 kg, body mass index (BMI) 24.7 ± 3.2 kg/m2, hematocrit 44 ± 3.2 %, and procedure time 84.2 ± 19.2 min. The median value of platelet yield was 3.2x1011 (2.1x1011 – 4x1011). The median value of pre-donation platelet count was 248.5x103/μL (204x103/μL – 391x103/μL) and the mean value of product volume was 275 ± 22.9 mL. The results showed that pre-donation platelet count (r = 0.329; p < 0.05) and product volume (r = 0.661; p < 0.05) positively correlated to the yield of platetetpheresis products. However, the yield of plateletpheresis products was not correlated to the post-transfusion platelet count (r = 0.327; p > 0.05). In conclusion, pre-donation platelet count and product volume of plateletpheresis influence the yield of plateletpheresis. However, the yield is not correlated to the post-donation platelet count. Thus, other clinical factors should be considered